Measurement of J/psi and psi(2S) polarization in pp collisions at sqrt[s] = 1.8 TeV. - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amendolia, SR; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Asakawa, T; et al. (2000)
We have measured the polarization of J/psi and psi(2S) mesons produced in pp collisions at sqrt[s] = 1.8 TeV, using data collected at the Collider Detector at Fermilab during 1992-1995. The polarization of promptly produced J/psi [psi(2S)] mesons is isolated from those produced in B-hadron decay, and measured over the kinematic range 4 [5.5]